Visto para nômade digital: uma análise da aplicação brasileira - Silva, Naará Maresha da (Universidade Federal de São Carlos, 2025)
The study analyzes the impact of digital nomadism on Brazilian tourism, focusing on the implementation of the visa for digital nomads, regulated by CNIG MJSP Resolution No. 45/2021. The main objective is to evaluate the legal implications and the potential economic, social, and cultural effects of this policy on the tourism sector. The research adopts an exploratory and descriptive approach, based on a bibliographic review, document analysis, and data provided by the International Migration Observatory. The results indicate that digital nomadism has emerged as a growing phenomenon, driven by the COVID-19 pandemic, which accelerated the adoption of remote work. The study highlights Brazil's potential to attract digital nomads due to its diverse destinations and favorable conditions offered by the visa. However, it identifies gaps such as bureaucracy and the need for greater investment in infrastructure and connectivity. Comparisons with policies in Portugal, Spain, and Thailand reveal best practices that could be adapted to the Brazilian context. The study concludes that digital nomadism positively impacts Brazilian tourism by fostering local economies and promoting cultural exchanges. Enhancing public policies is essential to maximize the benefits of this tourism modality and establish Brazil as a competitive destination for digital nomads.
Digital nomad visa: an analysis of the brazilian application
Keywords: Turismo; Nômade Digital; Trabalho Remoto; Nomadismo Digital; Políticas Públicas; Tourism; Digital Nomadism; Remote Work; Digital Nomad; Public Policies; CIENCIAS SOCIAIS APLICADAS::TURISMO